2017
DOI: 10.1038/s41598-017-10248-7
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Klein tunnel transistors for high speed analog RF applications

Abstract: We propose Graphene Klein tunnel transistors (GKTFET) as a way to enforce current saturation while maintaining large mobility for high speed radio frequency (RF) applications. The GKTFET consists of a sequence of angled graphene p-n junctions (GPNJs). Klein tunneling creates a collimation of electrons across each GPNJ, so that the lack of substantial overlap between transmission lobes across successive junctions creates a gate-tunable transport gap without significantly compromising the on-current. Electron sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…There may be ways to mitigate this problem with split gates that can align and misalign different parts of the Dirac cones independently. The application of this split-gate approach to graphene led to the design of a so-called Klein tunnel transistor [6,7], providphysics.aps.org c 2020 American Physical Society ing a way to modulate graphene's ultrahigh mobilities with modest voltages (∼ 1-2 V), with potential applications in high-speed analog devices [8]. Split-gate schemes may also be used to apply bi-directional torques to efficiently write information onto magnetic memory bits, as shown recently for 3D topological insulators [9].…”
mentioning
confidence: 99%
“…There may be ways to mitigate this problem with split gates that can align and misalign different parts of the Dirac cones independently. The application of this split-gate approach to graphene led to the design of a so-called Klein tunnel transistor [6,7], providphysics.aps.org c 2020 American Physical Society ing a way to modulate graphene's ultrahigh mobilities with modest voltages (∼ 1-2 V), with potential applications in high-speed analog devices [8]. Split-gate schemes may also be used to apply bi-directional torques to efficiently write information onto magnetic memory bits, as shown recently for 3D topological insulators [9].…”
mentioning
confidence: 99%
“…Sajjad et al have shown that such a GKT transistor would show a clean transport gap in the off state leading to a nearly ideal transfer characteristic consisting of low off current, high on-off ratio (I on /I of f =R of f /R on =10 4 ) and steep subthreshold swing (SS) lower than the Boltzmann limit of 60 mV/decade [2,4]. Beyond a desirable gate transfer characteristic, the GKT transistor was also shown to have an excellent output characteristic with a high saturating on current retaining a high mobility in the on state [7,15]. In these calculations [2,4,15] however, non-idealities such as momentum scattering, in particular at the edges were not considered.…”
mentioning
confidence: 99%
“…The output characteristic, however, bears more promise. At high drain bias (V DS ), a small transport gap (n + -n-n + , on state) at energies far from the equilibrium Fermi level is predicted to produce a strongly saturating I D -V D that is robust against edge roughness [7]. Even cases with an on-off ratio ∼10 can result in an order of magnitude increment in r out (output resistance) without hurting the mobility.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…fig. 3.5c) for analog high frequency applications and predict a 10-fold increase in the maximum operating frequency f max compared to a conventional graphene FET [196].…”
Section: Tilted Junctions and Electronic Switchesmentioning
confidence: 96%